Government Response to the Committee's 20th Report of Session 2017–19 : The Role of Parliament in the UK Constitution : Authorising the Use of Military Force : First Special Report of Session 2019 /: The Role of Parliament in the UK Constitution : Authorising the Use of Military Force : First Special Report of Session 2019. ([2019-11-01]) - Unknown
No abstract available